How To Differentiate Instruction : in Academically Diverse Classrooms. - Tomlinson, Carol Ann (ASCD, 2017)
First published in 1995 as How to Differentiate Instruction in Mixed-Ability Classrooms, this new edition reflects evolving best practices, practitioners' experience, and Tomlinson's ongoing thinking about how to help all students access high-quality curriculum; engage in meaningful learning experiences; and feel safe and valued in their school.